The Effect of Work Discipline and Work Motivation on Employee Performance in PT. Struktur Pracetak Nasional Jakarta - Lia Asmalah; Iis Noviyanti (Kusuma Negara Business School, 2021)
The purpose of this study was to determine the effect of work discipline and work motivation on the performance of employees of PT. Struktur Pracetak Nasional Jakarta, knowing work discipline and work motivation together on the performance of employees of PT. Struktur Pracetak Nasional Jakarta. The type of research used in this research is descriptive quantitative research. This study took a population of employees of the Project Manager of PT. Struktur Pracetak Nasional Jakarta consists of 54 people. The methods used are observation, interviews, and questionnaires. There are two sources of data used, namely primary data and secondary data. Primary data is data collected by researchers from respondents obtained online using google form. While secondary data is data collected by researchers obtained through literature and literature that will be discussed in research problems, reports and lecture materials. The research variables consist of independent variables or independent variables (X) namely work discipline (X1) and work motivation (X2) while the dependent variable or dependent variable (Y) is employee performance. The number of statement items is 18 consisting of a list of statements related to work discipline variables (X1), work motivation (X2) and employee performance (Y). The measurement scale used is a scale of 1 – 5 with 5 categories. The data analysis technique used in this study is through the SPSS calculation stages using IBM SPSS version 25, namely validity test, reliability test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression test, hypothesis test (partial t test and simultaneous f) test and coefficient of determination test. Work Discipline variables have a significant effect on Employee Performance. In the results of the t test, the results of the tcount > ttable are 5.842 > 2.008 and the significant value is 0.000 <0.05, then Ho is rejected and Ha is accepted. The variable of work motivation has a significant effect on employee performance. On the results of the t test, the results of the tcount > ttable are 5.807 > 2.008 and the significant value is 0.000 <0.05, so Ho is rejected and Ha is accepted. Variables of Work Discipline and Work Motivation have a significant effect on Employee Performance. In the results of the f test, the results of fcount > ftable are 127,004 > 3.18 and significant results are 0.000 < 0.05 then Ho is rejected and Ha is accepted, meaning that simultaneously or simultaneously the variables of Work Discipline and Work Motivation have a positive and significant effect on Employee Performance at PT. Struktur Pracetak Nasional Jakarta.